Cephalometrıc Evaluatıon Of Tongue In Varıous Malocclusıons - Ali Vehbi Tuncer; Erdal Işıksal; Servet Doğan (Galenos Yayinevi, 1991)
This study was accomplished to determine the tongue postures of 70 individuals, all showing the typical anatomic structures defining the malocclusion group they belong to. Cephalometric radiographs of 10 Class I, 10 Class II/2, 10 Open - bite, 20 Class II/1 and 20 Class III individuals were obtained for evaluation. Barium sulfate solution was applied to the tongue surfaces, cephalometric radiographs were taken during habitual occlusion and mandibular rest position. Cephalometric radiograph measurements were evaluated statistically. In all malocclusions, when the positional changes of tongue root and tongue dorsum were evaluated, the difference between mandibular rest position and habitual occlusion were found to be minimal. Changes of the tongue tip were insignficant in Class I and showed minimum significance in Class II/2 and Open - bite cases. During mandibular rest position the tongue tip was found more posterior in Class II/! than in Class III cases.